Isolated lymphatic vessel lumen perfusion system for assessing nanomaterial movements and nanomaterial-induced responses in lymphatic vessels. (February 2021) - Kuroda, Chika; Ajima, Kumiko; Ueda, Katsuya; Sobajima, Atsushi; Yoshida, Kazushige; Kamanaka, Takayuki; Sasaki, Jun; Ishida, Haruka; Haniu, Hisao; Okamoto, Masanori; Aoki, Kaoru; Kato, Hiroyuki; et al.
Graphical abstract: Highlights: Nanomaterials have recently been investigated for a wide variety of biological applications, including drug delivery and bioimaging. Nanomaterials are known to enter lymphatic vessels, migrate to the lymphatic system, and accumulate in lymph nodes. We have developed a novel ex vivo perfusion system to allow us to visually and quantitatively elucidate the interactions between nanomaterials and lymphatic vessels. Compared with in vivo models, this perfusion system allows more detailed examination of nanomaterial movement and lymphatic vessel reactions. The biokinetic discoveries made using this system are expected to contribute to the development of new biological nanomaterial applications. Abstract: Nanomaterials have recently been investigated extensively for a wide variety of biological applications, including drug delivery, bioimaging, and regenerative medicine. However, they have found little clinical use because of the lack of an established method for assessing their safety in living organisms. In particular, much remains unknown about the biokinetics of nanomaterials. Nanomaterials may be administered intravenously and reach various tissues via the bloodstream or injected directly into subcutaneous tissue or lesions such as tumors. These nanomaterials are known to enter lymphatic vessels, migrate to the lymph system, and accumulate in lymph nodes. To clarify their biokinetics, therefore, importance should be placed on elucidating their interactions with lymphatic vessels. However, little is known about their movements in, and influence on, the lymphatic vessels. In this study, we developed and assessed the isolated lymphatic vessel lumen perfusion system to allow us to visually and quantitatively elucidate the interactions between nanomaterials and lymphatic vessels, and thereby the biosafety of nanomaterials. The vessel is removed from a living rat and studied in vitro. This perfusion system, compared to in vivo examinations, allows higher-resolution, more detailed examination of the movement of nanomaterials and the lymphatic vessel's reaction to this movement. In addition, the new system also enables both quantitative and histological assessment of a single lymphatic vessel's physiological reaction to nanomaterials. Use of this system to provide essential information about nanomaterial biokinetics is expected to contribute significantly to the development of a wide variety of biological applications of nanomaterials.